Enhancing Arabic Learning Outcomes: A Study on the Effectiveness of Think-Pair-Share Model - Fadhilah, Amelya Khusnul; Ammar, Farikh Marzuqi (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the efficacy of the Think-Pair-Share learning model in enhancing Arabic language proficiency. A sample comprising 29 seventh-grade female students participated in the research. Data was gathered through observation, interviews, documentation, and pretest-posttest assessments using a one-group design. The N-gain test was employed for data analysis, providing a precise measure of improvement before and after the intervention. The results demonstrate a significant enhancement in Arabic learning outcomes, affirming the effectiveness of the Think-Pair-Share model. This research underscores the potential of interactive learning approaches for optimizing language education. Highlight: Empirical Study: Utilizing a one-group design, this research evaluates the impact of the Think-Pair-Share model on Arabic language proficiency among seventh-grade female students. Robust Methodology: Data collection encompasses a diverse range of methods including observation, interviews, documentation, and pretest-posttest assessments, ensuring comprehensive evaluation. Positive Outcomes: The results reveal a significant improvement in Arabic language learning, emphasizing the effectiveness of interactive learning strategies and advocating for their integration in language education. Keywrod: Arabic Language Proficiency, Think-Pair-Share Model, Interactive Learning, Language Education, Efficacy Assessment